Sitagliptin and Roux‐en‐Y gastric bypass modulate insulin secretion via regulation of intra‐islet PYY. Issue 3 (10th October 2017) - Guida, Claudia; McCulloch, Laura J.; Godazgar, Mahdieh; Stephen, Sam D.; Baker, Charlotte; Basco, Davide; Dong, Jiawen; Chen, Duan; Clark, Anne; Ramracheya, Reshma D
Abstract : Aims: The gut hormone peptide tyrosine tyrosine (PYY) is critical for maintaining islet integrity and restoring islet function following Roux‐en‐Y gastric bypass (RYGB). The expression of PYY and its receptors (NPYRs) in islets has been documented but not fully characterized. Modulation of islet PYY by the proteolytic enzyme dipeptidyl peptidase IV (DPP‐IV) has not been investigated and the impact of DPP‐IV inhibition on islet PYY function remains unexplored. Here we have addressed these gaps and their effects on glucose‐stimulated insulin secretion (GSIS). We have also investigated changes in pancreatic PYY in diabetes and following RYGB. Methods: Immunohistochemistry and gene expression analysis were used to assess PYY, NPYRs and DPP‐IV expression in rodent and human islets. DPP‐IV activity inhibition was achieved by sitagliptin. Secretion studies were used to test PYY and the effects of sitagliptin on insulin release, and the involvement of GLP‐1. Radioimmunoassays were used to measure hormone content in islets. Results: PYY and DPP‐IV localized in different cell types in islets while NPYR expression was confined to the beta‐cells. Chronic PYY application enhanced GSIS in rodent and diabetic human islets. DPP‐IV inhibition by sitagliptin potentiated GSIS; this was mediated by locally‐produced PYY, and not GLP‐1. Pancreatic PYY was markedly reduced in diabetes. RYGB strongly increased islet PYY content, but did not lead to full restoration of pancreatic GLP‐1 levels. Conclusion: Local regulation of pancreatic PYY, rather than GLP‐1, by DPP‐IV inhibition or RYGB can directly modulate the insulin secretory response to glucose, indicating a novel role of pancreatic PYY in diabetes and weight‐loss surgery.